Optoelectronic sensor of longitudinal and angular displacements - Dlugaszek, A.; Jabczynski, J.; Janucki, J.; Skrzeczanowski, W. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
In the sensor a triangulation method of displacement measurement has been used. A method of sensor calibration using interferometric distance measurements has been elaborated. Linearity and resolution investigations have been performed for different parameter sets of sensor transmitting-receiving head. An accuracy of displacement measurements depends on parameters of a beam illuminating a surface being displaced, parameters of a position sensitive detector and on a signal-to-noise ratio of a signal analog processing block. Results of investigations of uncertainties of lathe slide shifts are also presented.